BERTA’S FOOD STORY: THE CASE OF A SMALL SCALE GREEN BUSINESS IN YOGYAKARTA - Dewi, Novita; Siswanto, Fransiscus Asisi Joko; Anggraini, Francisca Reni (Sanata Dharma University, 2019)
This study seeks to examine the extent to which micro small and medium scale enterprises (MSMEs) apply Environmental Ethics in their business praxis. The data sources were field observations and in-depth interviews with one catering business in Yogyakarta known for its use of local food products and zero preservatives. This qualitative narrative research aims to answer how and why this selected MSME has demonstrated environmental awareness. It further examines the implications of this praxis toward the business’s sustainability. The data analysis reveals that, first, the business owner, driven by internal motivation, uses environmentally friendly products to care for customers’ satisfaction and need of healthy food. Secondly, the business, however, has not adhered to such external motivation as cutting no trees for firewood. Regardless of its damage for the environment, the use of firewood reduces production cost and no prohibition for cutting trees is thus far enacted. This study concludes that more efforts should be made to cultivate ecological concerns as the core of sustainable entrepreneurial skills.DOI:10.24071/ijhs.2019.030106